2014
DOI: 10.1002/lary.25006
|View full text |Cite
|
Sign up to set email alerts
|

Vocal fold pseudocyst: A prospective study of surgical outcomes

Abstract: Most individuals (15/17) returned to normal voice use without limitation after surgery. Some individuals appear predisposed to lesion recurrence, which occurs relatively swiftly. Demographic features and clinical variables are not predictive of recurrence. The role of glottic insufficiency related to recurrence warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…They report a pretreatment mean VHI-10 of 17.29 (the current study polyp group was 22.69), and they report a posttreatment VHI-10 of 5.12 (the current study polyp group was 7.19). 19 The present study showed a 20% increase in polyp diagnosis compared to our previous study, which resulted in subsequent changes to the incidence of surgical versus nonsurgical treatment. 3 Our previous data set had a 67% incidence of nonsurgical treatment compared to 33% for the present study.…”
Section: Discussionsupporting
confidence: 47%
See 4 more Smart Citations
“…They report a pretreatment mean VHI-10 of 17.29 (the current study polyp group was 22.69), and they report a posttreatment VHI-10 of 5.12 (the current study polyp group was 7.19). 19 The present study showed a 20% increase in polyp diagnosis compared to our previous study, which resulted in subsequent changes to the incidence of surgical versus nonsurgical treatment. 3 Our previous data set had a 67% incidence of nonsurgical treatment compared to 33% for the present study.…”
Section: Discussionsupporting
confidence: 47%
“…Similarly, Estes and Sulica reported a retrospective report of patients diagnosed and treated with “pseudocyst” in 2014 . This paper highlights the value of using a BMVFL nomenclature system that is comprehensive of all BMVFLs and use of strictly defined parameters that are not subjective.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations